1994
DOI: 10.3109/00016359409096375
|View full text |Cite
|
Sign up to set email alerts
|

Condylar height on panoramic radiographs: A methodologic study with a clinical application

Abstract: The aim of this study was to develop and apply a reliable method of measuring the effects of condylar lesions quantitatively on panoramic radiographs. Three different types of machines were tested. Two dry skulls were exposed in six positions in each machine, and the relative size of the condyle in relation to ramus height was calculated. The results showed good validity for the reference points used. The head position did not contribute to the variation in the measurements, but the type of panoramic machine h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
1
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 13 publications
1
73
1
14
Order By: Relevance
“…VCA is determined by comparing the vertical condylar height between the left and right condyle. Several techniques have been developed to evaluate this asymmetry, and the most common among them are developed by Kjellberg et al (1994) and Habets et al (1988). The objective of this study was to evaluate the similarity of the Habets' and Kjellberg's methods with regard to these results and analyze the VCA results of the temporomandibular joint in patients with signs and symptoms of TMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VCA is determined by comparing the vertical condylar height between the left and right condyle. Several techniques have been developed to evaluate this asymmetry, and the most common among them are developed by Kjellberg et al (1994) and Habets et al (1988). The objective of this study was to evaluate the similarity of the Habets' and Kjellberg's methods with regard to these results and analyze the VCA results of the temporomandibular joint in patients with signs and symptoms of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…ACV se determina al comparar la altura condilar vertical entre el cóndilo derecho e izquierdo. Se han desarrollado diversas técnicas para evaluar esta asimetría, las más conocidas son las desarrolladas por Kjellberg et al (1994) y Habets et al (1988). El Objetivo de éste estudio fue evaluar la similitud de la técnica de Habets con la técnica de Kjellberg en cuanto a los resultados y analizar éstos resultados de ACV de la articulación temporomandibular en pacientes con signos y síntomas de un trastorno temporomandibular.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The distortion from both the radiographs. Some authors [20,21] have suggested the use of ratio over the linear dimensions especially in radiographs where chances of inherent errors like distortion, magnification either due to projection geometry or due to patient positioning, shadows the accuracy in determining the right left differences or asymmetry. With respect to panoramic radiographs, Van Eslande [20] stated that by using the ratio, condylar height asymmetries can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…A radiografia panorâmica de face é um exame muito utilizado na avaliação do sistema mastigatório por dar uma visão geral de ossos maxilares, dentes e ATM 100 . É exame de simples execução, baixa radiação e baixo custo, porém não é um exame de muita precisão 2 , e pode apresentar erros quando se deseja realizar medidas 77 . Em AIJ, é utilizado na avaliação das alterações da ATM 13,65,66,71,77,94 , na avaliação de dentes e de dimensões condilares e mandibulares 70 .…”
Section: Disfunção Temporomandibular Em Pacientes Com Aijunclassified